Case report: Bilateral facial palsy with paresthesias and positive anti-GT1a antibodies - Xu, Xiaoxuan; Wang, Zhihan; Su, Chang; Cong, Lin; Zheng, Dongming (Frontiers in Immunology, 2024)
Bilateral facial palsy with paresthesia (FDP) is a rare variant of GBS, characterized by simultaneous bilateral facial palsy and paresthesia of the distal limbs. Mounting evidence indicates that the presence of anti-GT1a IgG has a pathogenic role as an effector molecule in the development of cranial nerve palsies in certain patients with GBS, whereas anti-GT1a antibody is rarely presented positive in FDP. Here, we report the case of a 33-year-old male diagnosed with FDP presented with acute onset of bilateral facial palsy and slight paresthesias at the feet as the only neurological manifestation. An antecedent infection with no identifiable reason for the fever or skin eruptions was noted in the patient. He also exhibited cerebrospinal fluid albuminocytologic dissociation and abnormal nerve conduction studies. Notably, the testing of specific serum anti-gangliosides showed positive anti-GT1a IgG/IgM Ab. The patient responded well to intravenous immunoglobulin therapy. This case brings awareness to a rare variant of GBS, and provides the first indication that anti-GT1a antibodies play a causative role in the development of FDP. The case also suggests that prompt management with IVIG should be implemented if FDP is diagnosed.